Coaching and its effects on individual and organizational performances in Central and Eastern Europe - Szilvia Szabó; Agneš Slavić; Nemanja Berber (Anali Ekonomskog fakulteta u Subotici, 2019)
Coaching as a skill for helping others grow and develop in the workplace has become a major asset in the life of profit-oriented organizations in recent decades. Coaching as a unique practice to develop the human resources of a company can create a partnership between a supervisor and an employee. The aim of the work is to analyze the effects of coaching on productivity and annual staff turnover based on Cranet research from 2015/16 from 9 countries of Central and Eastern European region. The results show that a higher level of the usage of coaching for career management in a company is positively related to the level of productivity and negatively related to the level of staff turnover. https://doi.org/10.5937/AnEkSub1941067S